Effects of the bendazol fungicide on in vitro development of the nim (Azadirachta indica A. JUSS) - dos Santos, Elisabete Pacheco; de Souza, Robson Antonio; Lacerda e Medeiros, Maria Jaislanny; Alves, Gilberto Dias; Houllou, Laureen Michelle (Research in Biotechnology, 2016)
Two experiments were conducted to evaluate Bendazol fungicidal effects in neem micropropagation. In these experiments, the nodal segment explants from in vitro plants were used. In the first experiment, the explants remained in DKW culture medium for a period of 30 days containing different concentrations of Bendazol (M1 -50, M2 - 100, M3 - 200, and M4 - 400 mg.L-1). The control treatment (M0) was prepared with DKW medium + BAP (0.225 mg.L-1). In the second experiment, the explants were maintained for only one week in media supplemented with Bendazol or BAP, and then they were transferred and kept in free Bendazol/BAP media for three weeks. In each experiment, the design was completely randomized with five treatments, 10 replicates per treatment, and one explant/cultivation flask. The variables analyzed included the formation of calluses and roots, lateral bud development, shoot height, contamination and plant death. There was no significant difference in tree variables (shoot, callus formation and shoot height) between treatments in both experiments. There was no death, plant contamination and rooting during the experiment. The results indicate that Bendazol can be used at low doses for in vitro neem cloning thereby replacing BAP and ultimately reducing production costs.